2022
DOI: 10.1007/s00701-022-05282-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for degenerative cervical myelopathy in the elderly: a nationwide registry-based observational study with patient-reported outcomes

Abstract: Background The aim of this study was to investigate whether clinical outcomes in patients aged ≥ 70 undergoing decompressive surgery for degenerative cervical myelopathy (DCM) differ from those of younger patients (50–70 years) at 1 year. Methods Data were obtained from the Norwegian Registry for Spine Surgery (NORspine). Among 651 patients included, 177 (27.2%) were ≥ 70 years old. The primary outcome was change in the Neck Disability Index (NDI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition to pain, physical disability, and health related quality of life, RTW is increasingly acknowledged as a core outcome measure in spine surgery [5,41]. Recent studies have shown considerable improved physical function after surgery for DCM which may provide new opportunities to patients who were previously unable to work [8,12,17]. Although surgery for DCM results in statistical and clinical meaningful improvement, this is not a guarantee for returning to work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to pain, physical disability, and health related quality of life, RTW is increasingly acknowledged as a core outcome measure in spine surgery [5,41]. Recent studies have shown considerable improved physical function after surgery for DCM which may provide new opportunities to patients who were previously unable to work [8,12,17]. Although surgery for DCM results in statistical and clinical meaningful improvement, this is not a guarantee for returning to work.…”
Section: Discussionmentioning
confidence: 99%
“…Neck and back pain are leading causes of absence from work [24,42]. Recent studies examining outcomes after surgery for DCM found significant improvement for both mild, moderate, and severe DCM measured with several different patient-reported outcome measures (PROMs) [12,17]. Due to the high relevance for the individual and society, return to work (RTW) has become an important outcome measure in recent years [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to a United Nations survey, the number of people of exceedingly advanced ages is increasing: the global population aged 80 years or older is projected to grow from 125 million in 2015 to 202 million in 2030 and to 434 million in 2050 [1]. Reports on surgical outcomes in elderly CM patients, especially those aged 80 years or older, have suggested that appropriate surgical results can be obtained if the patients were correctly selected and the procedures were properly performed [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is important to check for physical signs when diagnosing CM, because CM is a clinical diagnosis based on a history of myelopathic complaints, myelopathic signs on physical examinations, and advanced imaging studies showing correlative compression of the cervical spinal cord. Although several reports have described the clinical features and surgical outcomes of patients with elderly CM patients [2,3,[6][7][8], little is known about the prevalence of physical findings [9]. The purpose of this study was to examine the physical signs and clinical features of elderly patients with CM and compare the findings in three different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…It might be deferred as multi-variate logistic regression would capture the confounding effects of these factors, but the fact is that two groups have such difference, multiple regression analysis cannot account for the confounding factors. For such heterogeneous samples with large sample reserve available, doing propensity matching followed by stepwise regression model creation is more promising, as carried out on same or similar databases several times before [3][4][5][6]. In addition, there are some other variables that ideally are required to be in the models (yet NSQIP may not provide them) and should be considered in real world decision making.…”
mentioning
confidence: 99%